THE PROBLEM OF STROKE IN THE REPRESENTATION OF RESIDENTS - Novikova, L.B.; Latypova, R.F.; Solovyova, K.D.; Gabidullina, Yu.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background: acute cerebrovascular accident is the leading cause of disability and disability. Materials and methods: the article presents an analysis of testing the initial and control knowledge of 785 residents of various specialities of the first year of study at Bashkir State Medical University before and after passing the Stroke classes from March to April 2023 of the Department of Neurology at the Bashkir State Medical University. Results: a quantitative and qualitative analysis of respondents’ responses showed that residents are poorly aware of the risk factors for stroke, the strategy of primary and secondary prevention of stroke, the first signs of stroke, and first aid for stroke. After passing the Stroke classes, the results of residents improved significantly. Conclusions: thus, the results of the study indicate the need for educational programs on ONMK for residents of all specialities.